Pedagogical innovation process in technological strengthening in the agro-industrial sector (Agroindustria, Sociedad y Ambiente, 2023)
A documentary and bibliographical review was carried out by consulting scientific articles in scientific databases corresponding to the period between 2014-2022 referring to the development of technological tools such as virtual reality, augmented reality and robotics, which are tools that are key to the generation of technological skills in professionals in the agro-industrial field in Colombia. From this review, an analysis of the importance of pedagogy was carried out, for the generation of knowledge in aspects based on the use of technological tools. For this, several aspects will be addressed, such as which are the most used technological tools and whose applications are feasible in the agro-industrial field, what are the pedagogical strategies for teaching these skills, which are the key sectors of the Colombian agro-industrial sector that would benefit from the acquisition of these abilities and skills, what is the capacity and disposition of the Colombian agro-industrial sector for the adoption of technological innovations and what impact will these innovations have on the development of the sector. The analysis of the aspects addressed in this essay leads to the conclusion that the new skills of the agro-industrial professional in Colombia must have a high component of technological development in such a way as to generate more capacities that lead to a sustained growth of the sector in the near future.
Keywords: competences, digitization, skills, yield.